External Quality assessment of medical laboratories: requirements of MKS EN ISO 15189:2013 - Katerina Tosheska-Trajkovska (Institute of Knowledge Management, 2019)
Abstract: One of the main aspects of laboratory quality improvement is participation in external quality assessment schemes (EQAS), proficiency testing (PT) or interlaboratory comparisons (ILC). According to the requirements of the standard ISO EN 15189:2012, participation in EQAS is mandatory for each accredited laboratory. Accreditation is a formal recognition of eligibility to perform certain set of activities. National accreditation body (NAB) can monitor technical competence of the lab through participation in EQAS.Aim of the study: Assessment of the results of participation in EQAS for Biochemical Analyses Laboratory (BAL).Material and methods: BAL, within the Institute of Medical and Experimental Biochemistry, Medical Faculty-Skopje, is a medical laboratory accredited according to the International Standard MKC ISO EN 15189:2013. BAL participates in EQAS organized by Instand eV, Dusseldorf, Germany, since 2011. We analyze results of EQA after every survey. Institute for accreditation of the Republic of North Macedonia is NAB. As accredited laboratory, BAL has an obligation to fulfill two documents: plan for participation in EQAS/PT/ILC and review of participation (documents OB 05-18-2 and OB 05-18) and to present them to the lead assessor and technical assessor on annual basis during the on-site assessment of the laboratory.Results:Our laboratory participates in surveys for: haematology (differential blood count) and clinical chemistry (conventional analyses). Performance in the last 8 years varied by panel. Testing samples from each panel are sent to the BAL 3-4 times/year. There is variation in performance, with a best annual average performance in 2016 and 2017. Acceptancce criteria is +/-2SD.Except for haematology, annual performances for enrolled panels varied from year to year, indicating some difficulty in maintaining consistency in quality. The main challenges of the EQAS program observed between 2011 to 2019 were funding, sourcing, and safe transportation of quality panels to our laboratory. All these failures in the last years have helped us to significantly improve our overall quality of laboratory practices. Corrective and preventive actions are issuedfor outlying EQA results. By directing corrective measuresat root causes, we had realized that the likelihood of problem recurrence was minimized.Key benefit of participation in EQAS is improvement of the laboratory performance through: discovering of sources of error; systematic errors; demonstration of effectiveness of changes; common understanding of method differences; discovery of method sensitivities, etc.Conclusions: We therefore recommend all laboratories to participate in the EQAS program. Successful performance in an EQA programme reflects the effectiveness of the laboratory’s quality management. EQA is important for improvement of the laboratory quality management system, as it is a measure of laboratory performance
Keywords: accreditation; ISO 15189; medical laboratories; EQAS